2017
DOI: 10.5489/cuaj.4506
|View full text |Cite
|
Sign up to set email alerts
|

Can zero-hour cortical biopsy predict early graft outcomes after living donor renal transplantation?

Abstract: Introduction: The aim of this study was to identify relevance of subclinical pathological findings in the kidneys of living donors and correlate these with early graft renal function. Methods: This was a prospective study on 84 living donor kidney transplant recipients over a period of two years. In all the donors, cortical wedge biopsy was taken and sent for assessment of glomerular, mesangial, and tubule status. The graft function of patients with normal histology was compared with those of abnormal histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In a zero‐hour biopsy, a cortical wedge is taken immediately after revascularization on completion of vascular anastomosis. Zero‐hour renal allograft biopsy could be useful to evaluate subclinical renal lesions present in donors and pathological changes that are being transmitted from the donor to recipient via a grafted kidney . A previous report showed that these lesions are associated with renal prognosis and clinical findings .…”
mentioning
confidence: 99%
“…In a zero‐hour biopsy, a cortical wedge is taken immediately after revascularization on completion of vascular anastomosis. Zero‐hour renal allograft biopsy could be useful to evaluate subclinical renal lesions present in donors and pathological changes that are being transmitted from the donor to recipient via a grafted kidney . A previous report showed that these lesions are associated with renal prognosis and clinical findings .…”
mentioning
confidence: 99%
“…21 In a study of 84 donors in India, 48% had abnormal histological changes, which included glomerulosclerosis (25%), interstitial fibrosis (13%), acute tubular necrosis (5%), and focal tubular atrophy (5%). 22 The observed changes are not likely “hidden clues” to as yet unidentified mechanisms for LPHS but rather changes that can be observed in “normal kidneys.”…”
Section: Discussionmentioning
confidence: 97%
“…Such a unique pattern of gene expression may assist understanding how the status of donor biopsies may affect long-and short-term graft outcomes. [68][69][70][71][72] B cells and Ig/plasma cell transcripts are differentially expressed in TCMR, MIXED, and CAMR suggesting that a plasmacytic pathway is weak or absent in TCMR even though both T and B cells are present. A small subsets of NK transcripts is higher in CAMR/MIXED than TCMR (Figure 3A).…”
Section: Discussionmentioning
confidence: 99%